A novel lupene derivative from Thymus capitatus possesses an apoptosis-inducing effect via Let-7 miRNA/Cyclin D1/VEGF cascade in the A549 cell line - Nora M. Aborehab; Maha M. Salama; Shahira M. Ezzat (BMC, 2023)
Abstract Non-small-cell lung carcinoma (NSCLC) is a type of epithelial lung cancer accounting for about 85% of all lung cancers. In our research, a novel lupene derivative namely acetoxy-lup-5(6), 20(29)-diene (ALUP), as well as two known triterpenes; lupeol (LUP) and betulinic acid (BA) were isolated through the chromatographic purification of the 95% ethanolic extract of Thymus capitatus. Identification of the compounds was carried out by physicochemical properties as well as spectral 1D and 2D NMR analysis. The anti-cancer activity of the three triterpenes was assessed on non-small cell lung cancer cell line; A549 using MTT assay and cell cycle analysis using annexin V/propidium iodide. The molecular mechanism underlying anti-apoptotic effects was determined by analyzing Let-7 miRNA and miRNA-21 expression, the mRNA gene expression level of Bax, CASP-8, CD95, Bcl2, KRAS, VEGF, Cyclin D1 using qRT-PCR. Our results revealed that the three isolated compounds ALUP, LUP, and BA caused cell cycle arrest at the G2/M phase with an increase in the apoptosis which may be attributed to their significant effect on raising Bax, CASP-8, and CD95 and reducing the mRNA expression levels of Bcl-2, KRAS, VEGF, and Cyclin D1 compared to control cells. RT-PCR results showed that the ALUP, LUP, and BA significantly downregulated miRNA-21 expression. Meanwhile, the three compounds caused significant overexpression of Let-7 miRNA. This is the first report on the anti-cancer activity of acetoxy-lup-5(6), 20(29)-diene (ALUP) in reducing the proliferation and differentiation of the A549 cell line through inducing apoptosis. Finally, by targeting the Let-7 miRNA/Cyclin D1/VEGF cascade, acetoxy-lup-5(6), 20(29)-diene could be a potential therapeutic agent for lung cancer.